2022
DOI: 10.1159/000525917
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine and Clinical Outcomes in Peritoneal Dialysis: A Propensity-Matched Study

Abstract: <b><i>Introduction:</i></b> Telemedicine (TM) has shown to provide potential benefits on clinical outcomes in patients with chronic kidney disease but limited evidences published in the peritoneal dialysis (PD) population. This study aimed to explore the long-term effects of TM on the mortality and technique failure. <b><i>Methods:</i></b> The Peritoneal Dialysis Telemedicine-assisted Platform Cohort Study (PDTAP Study) was conducted prospectively in 27 hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Three studies were conducted in Mexico [ 29 , 30 , 31 ], two in Canada [ 32 , 33 ], two in China [ 10 , 34 ], and one each in Korea [ 35 ], the United Kingdom [ 11 ], Thailand [ 7 ], and Italy [ 36 ] ( Table 1 ). The study designs varied, with three using experimental designs (randomized controlled trials (RCTs) [ 10 , 32 , 35 ], six using observational–analytic designs [ 7 , 29 , 31 , 33 , 34 , 36 ], and two being observational–descriptive studies [ 11 , 30 ]. mHealth apps were used on various devices: 27.2% (3/11) on smartphones, 18.2% (2/11) on tablets, 9.1% (1/11) on computers, and 72.7% (8/11) on unspecified devices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies were conducted in Mexico [ 29 , 30 , 31 ], two in Canada [ 32 , 33 ], two in China [ 10 , 34 ], and one each in Korea [ 35 ], the United Kingdom [ 11 ], Thailand [ 7 ], and Italy [ 36 ] ( Table 1 ). The study designs varied, with three using experimental designs (randomized controlled trials (RCTs) [ 10 , 32 , 35 ], six using observational–analytic designs [ 7 , 29 , 31 , 33 , 34 , 36 ], and two being observational–descriptive studies [ 11 , 30 ]. mHealth apps were used on various devices: 27.2% (3/11) on smartphones, 18.2% (2/11) on tablets, 9.1% (1/11) on computers, and 72.7% (8/11) on unspecified devices.…”
Section: Resultsmentioning
confidence: 99%
“…For acceptance, which was studied in one study, positive results were reported [ 29 ]. Regarding effectiveness, a lesser number of patients from the intervention group switched from PD to HD or kidney transplantation compared with those from the control group [ 34 ]; however, three studies reported no significant differences [ 10 , 31 , 36 ]. In two studies, re-hospitalization rates showed no significant differences [ 10 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some of these data are automatically collected by the APD cycler, whereas some are dependent on patient or caregiver entry using dedicated equipment or a phone app. 40 Data are then reviewed by health care professionals, which may trigger actions such as remote changes of the dialysis prescription or direct support to the person doing PD either through phone calls or in-person review. This movement of data underpins the need for transparency with patients about the collection of data, alongside careful governance of the confidentiality and data security of all remote patient monitoring.…”
Section: Remote Patient Monitoringmentioning
confidence: 99%
“…41 The expected benefits of remote monitoring in PD arise from the greater support available for the person dialyzing at home, given that the inability to manage PD-related complications and the lack of specialist support are seen as a barrier to PD uptake. 42 Remote patient monitoring when used with APD has been shown in multicenter observational studies to lead to reduced rates of transfer to hemodialysis 40,43,44 and reduced hospitalization rates 44 possibly through improved adherence to therapy, reduction of patients and caregivers burnout, and early diagnosis of catheter dysfunction as well as high levels of patient satisfaction. 45,46 These studies are confounded by the increased uptake of monitoring in individuals with significantly higher levels of income, literacy, 40,47 comorbidity, 40 and shorter dialysis vintage 44 as well as industry support.…”
Section: Remote Patient Monitoringmentioning
confidence: 99%
See 1 more Smart Citation